Q) If the sum of first m terms of an A.P. is same as sum of its first n terms (m ≠ n), then show that the sum of its first (m + n) terms is zero.
Ans:
Step 1: We know that the sum of first m terms of an AP is given by:
Sm = (2 a + (m – 1) d)
Similarly, Sum of first n terms: Sn = (2 a + (n – 1) d)
By given condition, Sm = Sn
∴ (2 a + (m – 1) d) = (2 a + (n – 1) d)
∴ m (2 a + (m – 1) d) = n (2 a + (n – 1) d)
∴ 2 a m + m d (m – 1) = 2 a n + n d (n – 1)
∴ 2 a m + d m 2 – m d = 2 a n + d n 2 – n d
∴ 2 a m – 2 a n + d m 2 – d n 2 – m d + n d = 0
∴ 2 a (m – n ) + d (m 2 – n 2 ) – d (m – n) = 0
∴ 2 a (m – n ) + d (m – n) (m + n) – d (m – n) = 0
∴ (m – n ) (2 a + d (m + n) – d) = 0
∴ 2 a + (m + n – 1) d = 0 …………. (i)
Step 2: Sum of first (m + n) terms: S(m + n) = (2 a + (m + n – 1) d)
substituting the value of (m + n – 1) d from equation (i), we get:
S(m + n) = (0) = 0
Therefore, sum of first (m + n) terms is zero.
Please do press “Heart” button if you liked the solution.